(untitled) (Culturas Científicas, 2021)
Bayesian epistemology has simple conditionalization as its central concept. To understand in a good way how this rule operates, it is necessary to account for the subjective conception of probability. Based on the above, it is possible to clarify the scope and limits of simple conditionalization. In general, when this rule faces a difficulty, efforts are made to resolve this particular issue. Still, it is not usual to find unified proposals to resolve several of the complications underlying orthodox Bayesianism. Therefore, it is the purpose of this research to propose just that, an extended Bayesian framework that will aim to solve more than one issue, more specifically the incorrigibility problem, the zero raising problem, the old evidence problem, and the new theories problem. This will be achieved by adding to orthodox Bayesianism epsilon conditionalization and rational reconstruction.